Cooperative Quantum Phenomena in Light-Matter Platforms - Reitz, Michael; Sommer, Christian; Genes, Claudiu (PRX Quantum, 2022)
Quantum cooperativity is evident in light-matter platforms where quantum-emitter ensembles are interfaced with confined optical modes and are coupled via the ubiquitous electromagnetic quantum vacuum. Cooperative effects can find applications, among other areas, in topological quantum optics, in quantum metrology, or in quantum information. This tutorial provides a set of theoretical tools to tackle the behavior responsible for the onset of cooperativity by extending open quantum system dynamics methods, such as the master equation and quantum Langevin equations, to electron-photon interactions in strongly coupled and correlated quantum-emitter ensembles. The methods are illustrated on a wide range of current research topics such as the design of nanoscale coherent-light sources, highly reflective quantum metasurfaces, or low intracavity power superradiant lasers.
CRIS-Team WoS Importer:2022-02-04

Floquet engineering of molecular dynamics via infrared coupling - Reitz, Michael; Genes, Claudiu (Journal of Chemical Physics, 2020)
We discuss Floquet engineering of dissipative molecular systems through periodic driving of an infrared-active vibrational transition, either directly or via a cavity mode. Following a polaron quantum Langevin equation approach, we derive correlation functions and stationary quantities showing strongly modified optical response of the infrared-dressed molecule. The coherent excitation of molecular vibrational modes in combination with the modulation of electronic degrees of freedom due to vibronic coupling can lead to both enhanced vibronic coherence and control over vibrational sideband amplitudes. The additional coupling to an infrared cavity allows for the controlled suppression of undesired sidebands, an effect stemming from the Purcell enhancement of vibrational relaxation rates.
CRIS-Team WoS Importer:2021-01-22